The Utilization of the Insta-story Feature as a Tool to Build Self-Image in Students of the Faculty of Social and Political Sciences (FISIP) University of Lampung - Hidayati, Dewi Ayu; Irmasari, Heni (Universitas 17 Agustus 1945 Surabaya, 2024)
This study aims to describe how to use instastory features in shaping self-image and to describe the reasons users use instastory features in shaping self-image. This study used qualitative research methods. Informants in this study were 9 students from the Faculty of Social Sciences, University of Lampung with different majors. In addition, this study uses data collection techniques of observation, in-depth interviews, and documentation. Data analysis in this study uses data reduction, data presentation, and drawing conclusions and data verification. The results of this study show that: (1) Students of the University of Lampung Social Sciences before sharing photos or videos, always add edits to the uploaded photos or videos. Students also pay attention to appearance, give make- up before sharing photos or videos to the instastory. (2) University of Lampung Social Sciences students form a self-image in the institution with a variety of objectives, one of the reasons for forming self-image is because they want to be recognized in cyberspace and want to have a positive impact and desire to get a job offer. Keywords: Student, instastory, self-image. Abstrak Penelitian ini bertujuan untuk mendeskripsikan bagaimana penggunaan fitur instastory dalam membentuk citra diri serta untuk mendeskripsikan alasan pengguna menggunakan fitur instastory dalam membentuk citra diri. Peneliti menggunakan metode kulitatif. Informan pada penelitian ini berjumlah 9 orang mahasiswa Fisip Universitas Lampung dengan latar belakang jurusan yang berbeda. Selain itu, penelitian ini menggunakan teknik pengumpulan data observasi, wawancara mendalam, dan dokumentasi. Analisis data pada penelitian ini menggunakan reduksi data, penyajian data, serta penarikan kesimpulan dan verifikasi data. Hasil penelitian ini menunjukan: (1) Mahasiswa Fisip Universitas Lampung sebelum membagikan foto atau video, selalu menambahkan editan dalam foto atau video yang di unggah. Mahasiswa juga memperhatikan penampilan, memberikan polesan make-up sebelum membagikan foto atau video ke instastory. (2) Mahasiswa Fisip Universitas Lampung membentuk citra diri di instastory dengan tujuan yang beragam yang salah satu alasan membentuk citra diri yakni karena ingin di akui keberadaan nya di dunia maya serta ingin memberikan dampak positif dan keinginan untuk mendapatkan tawaran pekerjaan. Kata kunci : Mahasiswa, instastory, citra diri